Investigation of storage stability and in vitro digestion of nanoemulsions loaded carotenoids from Gracilaria dura, Sargassum acinarium and Ulva rigida macroalgae - Koşar, Maide; Arslan, Mustafa Enes; Mohammed, Aziz; Sarıbaş, Gamze; Durmaz, Gökhan; Okudan, Emine Şükran; Özçelik, Beraat; Uluata, Sibel; Yücetepe, Aysun (Springer Science and Business Media LLC, 2025)
This research determined the potential utilization of carotenoids extracted from macroalgae collected in the coastal water of Türkiye in the food industry. Carotenoids were extracted from Gracilaria dura, Sargassum acinarium and Ulva rigida collected from Türkiye seas by using ultrasound-assisted enzymatic extraction. Then, physical and storage stabilities of nanoemulsions including carotenoid and bioaccessibility of β-carotenoid during in vitro digestion were investigated. According to the study findings, carotenoid nanoemulsions were prepared with an encapsulation efficiency ranging approximately between 87% and 94%. The encapsulated carotenoids exhibited a superior ability to maintain stability in terms of both carotenoid content and antioxidant activity during in vitro digestion as compared to their non-encapsulated counterparts (p < 0.05). Chromatographic analysis of carotenoid profiles revealed the presence of β-carotene in nanoemulsions derived from Gracilaria dura, Sargassum acinarium and Ulva rigida. A reduction in the amount of β-carotene was observed in the nanoemulsions during in vitro digestion (p < 0.05). Results from the storage stability study indicate that the oxidative stability of algal carotenoid nanoemulsions was better than that of the control (p < 0.05). Conversely, destabilization occurred in algal carotenoid nanoemulsions on the seventh day of storage due to creaming. Lightness (L*) and color intensity (a*, b*) of the nanoemulsions gradually decreased over the 28-day storage period (p < 0.05). This study emphasizes the potential application of carotenoids from Gracilaria dura, Sargassum acinarium and Ulva rigida macroalgae in food products.
Keywords: Macroalgae; Emulsion; In Vitro Digestion; Carotenoids; Stability